2020
DOI: 10.1155/2020/9072637
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Location of Multiple Tuned Mass Dampers in Regular and Irregular Tall Steel Buildings Plan

Abstract: Tuned mass dampers are one of the most common devices for the passive control of structures subjected to earthquakes. The structure of these dampers consists of three main parameters: mass, damping, and stiffness. Tuned mass dampers reduce the amplitude of the responses affecting on a mode. In most cases, only a single TMD (tuned mass damper) or a few dampers at several points above the building height are installed on the roof of the building, requiring considerable mass and space in some parts of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Jin et al (2016) minimized the response of the beam by applying inerter-based passive vibration control systems and found that their performance was better than traditional dynamic vibration strategies. Khazaei et al (2020) studied the e ciency of vibration control in regular and irregular high-rise steel structures with multiple tuned mass dampers (MTMDs) using a passive approach. The results showed that the success of MTMDs depends on the symmetry of the TMDs relative to the center of mass of the structures.…”
Section: Passive Approachesmentioning
confidence: 99%
“…Jin et al (2016) minimized the response of the beam by applying inerter-based passive vibration control systems and found that their performance was better than traditional dynamic vibration strategies. Khazaei et al (2020) studied the e ciency of vibration control in regular and irregular high-rise steel structures with multiple tuned mass dampers (MTMDs) using a passive approach. The results showed that the success of MTMDs depends on the symmetry of the TMDs relative to the center of mass of the structures.…”
Section: Passive Approachesmentioning
confidence: 99%
“…In addition, [20] and [21] also recommended that the vibration control of multiple TMDs is more efficient when the dampers are strategically placed to the structural floors with the maximum amplitude in the mode shapes accordingly. [22] and [23] concluded from their study on the optimization of multiple TMD that by increasing the number of TMDs, the frequency ratio bandwidth becomes wider and decreases equivalent damping ratio subsequently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e numerical evaluations using different load patterns showed remarkable improvement compared with passive and nonmoving devices. In control systems, accurate computing with the lowest computational cost is an important advantage [22].…”
Section: Introductionmentioning
confidence: 99%